Modeling of an Energy Hybrid System Integrating Several Storage Technologies: The DBS Technique in a Nanogrid Application - Roberto Ciavarella (Sustainability, 2021)
Hybrid Systems in microgrid applications have gained relevance in power flow management in the context of the worldwide power grids transformation. Successfully integrating several technologies of micro resources and storage systems is a key component of microgrid applications. To address this issue, dc-bus signaling (DBS) is proposed here and used as a distributed decentralized control strategy in which the control nodes, as the generation sources/storage interface converters, induce DC bus voltage-level changes to communicate with the other control nodes. The DC bus voltage thresholds are identified and assigned to each converter to trigger the point at which it begins discharging or charging for six different DC Nano Grid (DCNG) configurations, thereby integrating both conventional and unconventional storage systems. Several test cases have been analyzed to verify the effectiveness of the proposed control logic.